Asymptotic analysis for hedging errors in models with respect to geometric fractional Brownian motion. Issue 3 (3rd April 2019) - Wang, Wensheng
ABSTRACT: In this paper, we investigate asymptotic behaviour for rates of discrete time hedging errors in models with respect to geometric fractional Brownian motion with Hurst parameterH > 1 2 . We analyse the rates of hedging errors due to discrete time trading when the true strategy is known, and the exact rates of convergence and limit distributions of hedging errors for models with respect to the fractional pathwise integral and the fractional Wick–Itô–Skorohod integral are investigated.